Spine morphogenesis in newborn granule cells is differentially regulated in the outer and middle molecular layers. Issue 12 (17th April 2014) - Zhao, Chunmei; Jou, Jessica; Wolff, Lisa J.; Sun, Huaiyu; Gage, Fred H.
ABSTRACT New neurons are continuously added to the hippocampus of adult mammals. Their survival and integration into the circuitry are highly dependent on experience. Here we show that mushroom spine formation in newborn granule cells was modulated by experience and that dendritic segments in different areas of the molecular layer were differentially regulated. Specifically, spines of new neurons in the outer molecular layer of the dentate gyrus were more readily influenced by nonspatial features in the living environment. Those in the middle molecular layer were more likely to be influenced by the size of the living environment. Therefore, the activity of cortical inputs into newborn granule cells may be reflected in the formation of mushroom spines in different dendritic segments in the molecular layer. J. Comp. Neurol. 522:2756–2766, 2014. © 2014 Wiley Periodicals, Inc.